2015
DOI: 10.1111/pbi.12360
|View full text |Cite
|
Sign up to set email alerts
|

Rice endosperm produces an underglycosylated and potent form of the HIV‐neutralizing monoclonal antibody 2G12

Abstract: SummaryProtein microbicides against HIV can help to prevent infection but they are required in large, repetitive doses. This makes current fermenter-based production systems prohibitively expensive. Plants are advantageous as production platforms because they offer a safe, economical and scalable alternative, and cereals such as rice are particularly attractive because they could allow pharmaceutical proteins to be produced economically and on a large scale in developing countries. Pharmaceutical proteins can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 82 publications
3
31
0
2
Order By: Relevance
“…The production of 2G12 has previously been reported in plants although only thus far in the context of proof-of-principle studies that do not address the requirements of process-scale GMP manufacturing. The antibody has been expressed in transgenic maize seeds Ramessar et al, 2008), Arabidopsis seeds and leaves (Loos et al, 2011), tobacco leaves (Floss et al, 2009;Strasser et al, 2008), and most recently rice seeds (Vamvaka et al, 2015) with similar in vitro biding activity as C2G12 and variable HIV-neutralization efficacy. It has also been produced, along with a panel of other HIV-neutralizing antibodies, by transient expression (Rosenberg et al, 2013;Sainsbury et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The production of 2G12 has previously been reported in plants although only thus far in the context of proof-of-principle studies that do not address the requirements of process-scale GMP manufacturing. The antibody has been expressed in transgenic maize seeds Ramessar et al, 2008), Arabidopsis seeds and leaves (Loos et al, 2011), tobacco leaves (Floss et al, 2009;Strasser et al, 2008), and most recently rice seeds (Vamvaka et al, 2015) with similar in vitro biding activity as C2G12 and variable HIV-neutralization efficacy. It has also been produced, along with a panel of other HIV-neutralizing antibodies, by transient expression (Rosenberg et al, 2013;Sainsbury et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vamvaka et al [74] reported the development of transgenic rice plant expressing the HIV-neutralizing antibody 2G12 in the endosperm (42 µg/g dry seed weight) to evaluate the potential of rice seeds as a vehicle for inexpensive microbicide production. Production is higher than the initial achievement of maize-derived 2G12 (30 µg/g) by Rademacher et al [156].…”
Section: Studies On Plant Vaccinesmentioning
confidence: 99%
“…Both activities have been detected in mature barley seeds, and there is a positive correlation between the removal of N-glycans from proteins and the mobilization of storage glycoproteins, reflecting the fact that both ENGase and PNGase activities increase during germination (Vuylsteker et al, 2000). Recombinant glycoproteins produced in cereal grains often carry a single GlcNAc linked to the asparagine residue, possibly reflecting endogenous ENGase activity (Rademacher et al, 2008; Hensel et al, 2015; Vamvaka et al, 2016). …”
Section: Introductionmentioning
confidence: 99%